Response, Peace-Loving Characters and Homeland Love Characters: Integrating Traditional Game of Petak Umpet - Asrial Asrial; Syahrial Syahrial; Dwi Agus Kurniawan; Muhammad Dewa Zulkhi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The purpose of this research was to integrate the traditional games of Petak Umpet into learning process. This type of research a mix method that is qualitative and quantitatif. This study involved several variables as a category of research namely the response, the character of peace-loving and the character of homeland. The sample of research was 44 students. Analyzing data used descriptive and inferential statistics. The result showed that integration was carried out at State of Elementary School 64 Muara Bulian and Madrasah Ibtidaiyah 4 Batang Hari seen in the response, the character of peace-loving and the character of love of the homeland. As a result each variable of the response, the character of Peace love and the character of love of the motherland has a significant comparison, with a value of sig<0.05 and on each dominant variable in the good category. The integration of traditional games in learning can be used as an alternative to fun learning and in accordance with the age of elementary school children. Keywords: Learning Traditional Games, Traditional Games, Petak Umpet Game